Linking Variation in Penguin Responses to Pedestrian Activity for Best Practice Management on Subantarctic Macquarie Island - Holmes, ND; Giese, M; Kriwoken, LK (Alfred-Wegener-Institute for Polar and Marine Research and the German Society of Polar Research, 2008)
From 20012005, a project was undertaken on subantarcticMacquarie Island to investigate the variation in responses to pedestrianactivity by King Aptenodytes patagonicus, Gentoo Pygoscelis papua andRoyal Eudyptes schlegeli penguins. The overall aim was to produce management-oriented information both for commercial tourism in the subantarcticand Antarctic, and for Antarctic Treaty Consultative Parties. A series of experimentaland observational studies were employed to quantify aspects ofphysiology, behaviour and reproductive success of these three species ofsubantarctic penguins when exposed to pedestrian activity the most commonform of human activity on Macquarie Island. Key aspects of penguin ecologylikely to yield information valuable to management were investigated, including:1) the efficacy of current minimum approach distance guidelines forvisitation to penguins; 2) the effect of visitor group size on penguin responsesto pedestrian activity; 3) the role of habituation in penguin responses to pedestrianactivity; 4) the phase of breeding / moult during which penguins are mostsensitive to pedestrian activity; and 5) comparative responses to humanactivity between the three species examined. This paper describes key resultsfrom these five studies, and the application for management of humanpenguininteractions on Macquarie Island and other subantarctic and Antarcticlocations.